1992
DOI: 10.1037/0021-843x.101.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Childhood depression and conduct disorder: II. An analysis of family interaction patterns in the home.

Abstract: Few researchers have assessed family interaction patterns associated with childhood depression, especially using observations in natural settings. We directly sampled the interaction patterns of families with depressed, conduct-disordered, mixed depressed-conduct-disordered, and comparison children ages 7-14 years in their homes during the evening meal. Observational measures were taken of positive and aversive behaviors and affect expression for both parents, the referred children, and their siblings. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1
6

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 14 publications
7
92
1
6
Order By: Relevance
“…Finally, further research is needed that assesses family interaction patterns associated with childhood depression and conduct disorder in naturalistic settings. In the article by Dadds, Sanders, Morrison, & Rebgetz (1992) in this issue, the assessment of family interactions during the evening meal is described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, further research is needed that assesses family interaction patterns associated with childhood depression and conduct disorder in naturalistic settings. In the article by Dadds, Sanders, Morrison, & Rebgetz (1992) in this issue, the assessment of family interactions during the evening meal is described.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies in which these methods have been used to assess depressed children. In the present study, we used structured clinic observations of interaction patterns during family problem-solving discussions, and in a second study (Dadds, Sanders, Morrison, & Rebgetz, 1992) reported elsewhere in this issue, we used naturalistic mealtime observations. Several authors have argued for the importance of problem-solving skills in the treatment of behavioral and emotional disturbance in children and adolescents (Alexander, 1973;Borduin et al, 1985;Dodge, 1985; Kazdin, Esveldt-Dawson, French, & Unis, 1987; Kendall & Braswell, 1985;Robin, 1981).…”
mentioning
confidence: 99%
“…Because many studies have examined parent-child interactions in only one interaction task (e.g., Dadds, Sanders, Morrison, & Rebgetz, 1992) or have combined data across different tasks (Ge, Best, Conger, & Simons, 1996), little is known about the relation between parenting behavior in specific tasks and child psychopathology. Insofar as different studies have assessed the same parenting behavior but in different interaction tasks, cross-study comparisons may suggest that these parenting behaviors have non-specific effects when in fact their effects are specific to the particular interaction within which the parenting behavior occurs.…”
mentioning
confidence: 99%
“…D'une part, des résultats indiquent que les parents d'élèves qui présentent à la fois des troubles intériorisés et extériorisés ont une relation davantage négative avec leur enfant que ceux d'élèves qui n'ont que l'un ou l'autre de ces troubles (Capaldi, 1991 ;Ge, Best, Conger et Simons, 1996 ;Marmorstein et Iacono 2004). D'autre part, des études montrent que la qualité de la relation parent-enfant dans le groupe où il y a concomitance des troubles est semblable à celle du groupe où les troubles sont extériorisés (Dadds, Sanders, Morrison et Rebgetz, 1992 ;Kim, Ge, Brody, Conger, Gibbons et Simons, 2003), voire meilleure (Sanders, Dadds, Johnston et Cash, 1992), cette relation étant toutefois moins bonne que celle observée lorsque les jeunes n'ont qu'un trouble intériorisé. Cependant, d'autres études ne révèlent pas de différence entre ces trois groupes, bien que ces relations demeurent plus négatives que celles observées chez les enfants n'ayant aucun trouble du comportement (Fortin et al, 2000 ;Talbot et Fleming, 2003).…”
Section: Facteurs De Risque Et Cooccurrence Des Troubles Intériorisésunclassified
“…Fortin et al (2000) ainsi que Talbot et Fleming (2003) observent aussi des résultats assez similaires entre ces groupes pour ce qui est des caractéristiques de la relation parent-enfant. Cependant, tout comme dans les études de Capaldi (1991), Dadds et al (1992), Kim et al (2003), Marmorstein et Iacono (2004) et Sanders et al (1992), nos résultats suggèrent que lorsqu'il y a des différences entre les groupes, celles-ci sont surtout à l'effet que les caractéristiques familiales du groupe « concomitant » sont plus problématiques que celles du groupe n'ayant que des troubles intériorisés. Dans la plupart de ces études, cependant, le groupe concomitant et le groupe aux problèmes extériorisés présentent des caractéristiques démographiques, parentales et de la relation parent-enfant assez similaires.…”
Section: Caractéristiques De La Relation Parent-enfantunclassified